THE SPECTROPHOTOMETRIC OBSERVATIONS OF THE SUNSPOTS - N. V. Lisichkina; J. G. Goloktionova (Современная наука и инновации, 2022)
The natural resources of the region are one of the most important components of its tourist and recreational potential. Therefore, the regional system of strategic management should be based on the concept of sustainable development, in which the effectiveness of management decisions is evaluated by the criterion of minimizing negative environmental and social consequences, including deferred ones. To develop such a management system in conditions of uncertainty, it seems appropriate to use a synergetic-institutional approach.